Controlled Nanopores in Thin Films of Nonstoichiometrically Supramolecularly Assembled Graft Copolymers. Issue 50 (27th October 2015) - Cho, Suk Man; Song, Giyoung; Hwang, Sun Kak; Kim, Richard Hahnkee; Lee, Jinseong; Yu, Seunggun; Huh, June; Park, Hui Joon; Park, Cheolmin
Abstract: Herein, nanometer‐scale morphologies of graft‐copolymer‐like supramolecular thin films, composed of sulfonic acid terminated polystyrene (SPS) and poly(2‐vinylpyridine) (P2VP), and their application to antireflection coatings were investigated. The intermolecular complexes of SPS and P2VP, formed through nonstoichiometric multiple hydrogen bonding between the sulfonic acid group of SPS and the nitrogen atom in pyridine unit of P2VP, occurring in film deposition allowed for the formation of spherical micelles (with SPS and P2VP as the corona and core, respectively) in the thin film. Interestingly, the domain size of the micelles was tunable from approximately 20 to 90 nm on average by controlling either the blend ratio of components or the concentration of polymer solution. Furthermore, nanoporous thin films could be easily prepared by removing the core of micelle‐based nanostructures by using a simple solvent etching process, leaving sulfonic acid groups on the surface of nanopores, which can be utilized as potential functional sites. Those resultant nanoporous thin films were conveniently employed as an antireflection layer on a glass substrate, giving a maximum 97.8 % transmittance in the visible wavelength range. Abstract : Hard graft! The graft‐copolymer‐like supramolecular assembly of an end‐functionalized polymer and a homopolymer blend, based on nonstoichiometric hydrogen bonding, offers size‐controllable nanopores. The resultant films were employed as an antireflection layer on a glass substrate, which gave rise to excellent visible‐light transmittance (see figure).